The reform of prisoners, 1830-1900 - Forsythe, William James.
1 online resource.
Keywords: This study, first published in 1987, focuses on Victorian approaches to the moral reformation of prisoners, and aims to emphasise the ways in which the human value and social inclusion of prisoners were pursued. The author begins by discussing the evangelical view of social problems and human value in early-industrial Britain as well as the associationist' psychological analysis of human attitude developed by theorists from John Locke to Jeremy Bentham. The workings of these two theoretical frameworks in the practice of British prisons are then analyses, arguing that by 1860 both theories were basic to the approach to the incarceration of wrongdoers. After 1860 the picture changed radically to an unambiguous deterrent severity. This was linked to a more scientific' and evolutionist analysis of human conduct and attitude; theological objections to reformism were also brought into play. In the last forty years of the nineteenth century prisoners came to be seen as constitutionally inferior beings for whom no hope of reform could be generally entertained. This title will be of interest to students of history and of criminology.